2022
DOI: 10.1007/s00259-022-05704-0
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy and clinical impact of FDG-PET/CT follow-up for patients on adjuvant immunotherapy for high-risk malignant melanoma

Abstract: Objective The benefit of FDG-PET/CT in follow-up of patients treated with adjuvant immunotherapy after resection of highrisk malignant melanoma (MM) is debated. This study evaluated the diagnostic accuracy and clinical impact of FDG-PET/ CT for diagnosing MM recurrence during the first year after surgery. Methods We retrospectively included 124 patients with resected high-risk MM, who received adjuvant immunotherapy and follow-up FDG-PET/CT. Clinical information and AJCC-8 stage was obtained from patients' med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…During the full text review of the remaining 372 articles, 269 were considered ineligible based on the above-mentioned selection criteria. Finally, 100 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the full text review of the remaining 372 articles, 269 were considered ineligible based on the above-mentioned selection criteria. Finally, 100 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ...…”
Section: Resultsmentioning
confidence: 99%
“… Forest plots for the pooled sensitivity and specificity calculation for secondary staging at the patient level. Horizontal lines represent 95% confidence intervals of the individual studies [ 14 , 16 , 17 , 19 , 21 , 22 , 23 , 40 , 54 , 60 , 65 , 66 , 67 , 69 , 71 , 72 , 75 , 78 , 91 , 97 , 101 , 108 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Generally, patients with metastatic MM of the stomach have atypical clinical symptoms ( 11 ), including abdominal distension, acid reflux, and other symptoms, as well as complications such as bleeding and perforation ( 12 ). They are easy to be confused with various benign and malignant diseases of the digestive tract, resulting in missed diagnosis and misdiagnosis and missing the best treatment period ( 13 ). Therefore, if the patient has a history of surgical resection of “melanoma” in the past, finds black tumors in the skin and mucosa during physical examination, and is hospitalized due to digestive system symptoms, MM should be highly suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established the value of cross-sectional imaging, particularly PET and PET/CT, in the staging of malignant melanoma. It has been previously demonstrated that the use of PET/CT is highly diagnostic for the evaluation of N-and M-staging, response to therapy and recurrence (15)(16)(17)(18). Additionally, a metaanalysis by Schroer-Gunther et al demonstrated increasing prognostic accuracy with increasing stage in the use of crosssectional imaging (19).…”
Section: Discussionmentioning
confidence: 99%